Determinación de la acción del hongo entomopatógeno a la broca del café (hipotenemus hampei), en la región San Martín. - Philco Balvin, Carlos Eduardo (2001)
The present study was conducted in the laboratory of plant pathology at the Institute of tropical crops, between the months of June to December 2000, in order to determine isolates entomopathogenic fungi against the bit of coffee. 16 native isolates of the fungus (MJA, RNA, MJAB, LPA, RAA, TCA, LPB, CBT, LZB, LZA, LPD, RPA, TCB, LPC, TCD and LZC) were obtained. which were collected from different localities in the Department of San Martin, then proceeded with the following methodology: collected cherry of the coffee field which were infested by the bit and turn the bit infected by the fungus, were carried to the laboratory, where he became a disinfection with sodium hypochlorite at the 0.5%,durante 1 to minutes, then dry it in paper towel sterile proceeded to sown in Petri dishes that merely Pope dextrose, and hagar. The fungus was developed, then, became radial growth rate assessments, qualitative characteristics. count of conidia, germination percentage, percentage of sporulation and the percentage of mortality of bits. Selecting insulation LPA, as the best of all by having a control aggressive front bits (46 to 72 hours), from the Lamas province, Pamashto and Caserlo of Bellavista district. Results of significant differences between one and another insulation